2003
DOI: 10.1002/cne.10553
|View full text |Cite
|
Sign up to set email alerts
|

Inner S‐cone bipolar cells provide all of the central elements for S cones in macaque retina

Abstract: Synaptic terminals of cones (pedicles) are presynaptic to numerous processes that arise from the dendrites of many types of bipolar cell. One kind of process, a central element, reaches deeply into invaginations of the cone pedicle just below an active zone associated with a synaptic ribbon. By reconstruction from serial electron micrographs, we show that L- and M-cone pedicles in macaque fovea are presynaptic to approximately 20 central elements that arise from two types of inner (invaginating) bipolar cell, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 63 publications
(113 reference statements)
7
54
1
Order By: Relevance
“…Our material had only 12 inner S-cone bipolar cells, so their density, 2702 cells mm Ϫ2 , might not have been perfectly accurate as well. As shown by Herr et al (2003) for this patch of retina, in agreement with findings of Kouyama and Marshak (1997), there are ;2 inner S-cone bipolar cells for each S cone. Our density values were compatible with that finding.…”
Section: Comparison Of the Densities Of Inl Cells And Cone Pediclessupporting
confidence: 89%
See 3 more Smart Citations
“…Our material had only 12 inner S-cone bipolar cells, so their density, 2702 cells mm Ϫ2 , might not have been perfectly accurate as well. As shown by Herr et al (2003) for this patch of retina, in agreement with findings of Kouyama and Marshak (1997), there are ;2 inner S-cone bipolar cells for each S cone. Our density values were compatible with that finding.…”
Section: Comparison Of the Densities Of Inl Cells And Cone Pediclessupporting
confidence: 89%
“…There and elsewhere (Klug et al, 1992;Herr et al, 2003) we have reported that L and M cones contacted their own inner midget bipolar cells, whereas S cones did not. By contrast, S cones as well as other cones contacted outer midget bipolar cells (Klug et al, 1992).…”
Section: Midget Bipolar Cells-the Rule and The Exceptionsupporting
confidence: 55%
See 2 more Smart Citations
“…1 A) and S cone 52 (see Fig. 1 B), as described by Herr et al (2003). First, from each section, we traced the contour of the presynaptic face of the S-cone terminal by hand onto a clear plastic sheet (Herr et al, 2003, compare their Fig.…”
Section: Methodsmentioning
confidence: 99%